When and how did you go wrong? Characterizing mild functional difficulties in older adults during an everyday task. Issue 2 (4th March 2021) - Divers, Ross; Ham, Lillian; Matchanova, Anastasia; Hackett, Katherine; Mis, Rachel; Howard, Kia; Rycroft, Sarah Seligman; Roll, Emily; Giovannetti, Tania
ABSTRACT: Mild functional difficulties associated with cognitive aging may be reliably measured by coding "micro-errors" during everyday tasks, like meal preparation. Micro-errors made by 25 older adult and 48 younger adults were coded on four dimensions to evaluate the influence of: 1) poor error monitoring; 2) goal decay; 3) competition for response selection when switching to a new subtask; and 4) interference from distractor objects. Micro-errors made by young adults under a dual task load also were analyzed to determine the influence of overall performance level. Older adults' micro-errors were observed when switching to a new subtask and to unrelated distractors. Slowed error monitoring and goal decay also influenced micro-errors in older adults, but not significantly more so than younger adults under the dual task. Interventions to reduce interference from distractors and to increase attention at critical choice points during tasks may optimize everyday functioning and preclude decline in older adults.